2017
DOI: 10.3389/fneur.2017.00295
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Impairments in Patients with the Norrbottnian Form of Gaucher’s Disease Type 3

Abstract: BackgroundChronic neuronopathic Gaucher’s disease type 3 (GD3) is relatively frequent in northern Sweden. Besides multiple other neurological symptoms, horizontal gaze palsy or oculomotor apraxia is common in GD3.ObjectiveTo characterize the saccades in patients with Norrbottnian GD3 with respect to their neurological and cognitive status using a computer-based eye-tracking technique.MethodsHorizontal and vertical reflexive saccades as well as antisaccades of nine GD3 patients [4M/5F; 41.1 ± 11.0 years; modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 16 publications
5
13
1
Order By: Relevance
“…This study was undertaken to evaluate the use of video-oculography as a tool to measure saccadic eye movement parameters in Gaucher Disease. We have replicated the previously reported data showing lower peak velocity in horizontal and vertical saccadic eye movements in nGD patients versus a control cohort [13,17,23,24]; although the specific values in the cohort are slightly higher than those reported by Bremova-Ertl et al [17] the difference between the values is consistent. The ability to replicate data findings between disease states is supportive of a role for such a device for clinical use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study was undertaken to evaluate the use of video-oculography as a tool to measure saccadic eye movement parameters in Gaucher Disease. We have replicated the previously reported data showing lower peak velocity in horizontal and vertical saccadic eye movements in nGD patients versus a control cohort [13,17,23,24]; although the specific values in the cohort are slightly higher than those reported by Bremova-Ertl et al [17] the difference between the values is consistent. The ability to replicate data findings between disease states is supportive of a role for such a device for clinical use.…”
Section: Discussionsupporting
confidence: 90%
“…The modified Severity Scoring Tool (mSST)[32] was designed and implemented as a clinical tool for this purpose and has shown utility, however a component of the tool includes saccadic eye movement deficits and the cohort presented here with objective measures with neuronopathic disease was small. Correlation has been demonstrated with vertical saccade duration and mSST previously[17,23] but a larger cohort study is required and ideally a more detailed scoring tool or biomarker to demonstrate CNS involvement.LimitationsA larger cohort of control data confirming any subtly differences in saccade parameters by age would be of value. Observations from this cohort of controls may not have been adequately powered to demonstrate significant statistical difference by age; however previous studies (using various devices to measure saccadic movements) have shown that with increasing age, peak saccade velocity is reduced…”
mentioning
confidence: 99%
“…The modified Severity Scoring Tool (mSST) [38] was designed and implemented as a clinical tool for this purpose and has shown utility, however a component of the tool includes saccadic eye movement deficits and the cohort presented here with objective measures with neuronopathic disease was small. Correlation has been demonstrated with vertical saccade duration and mSST previously [18,24] but a larger cohort study is required and ideally a more detailed scoring tool or biomarker to demonstrate CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular motor apraxia, which in fact reflects abnormal patterns of head motion associated with defects in initiation of saccades, is also observed in Gaucher's types 2 and 3 . Similar to NP‐C, patterns of abnormal saccades can be used to monitor progression of disease . Gaucher's disease type 1 is the chronic non‐neurological form; however, subtle slowness of saccades has been reported in some patients .…”
Section: Inborn Errors Of Metabolism Associated With Ocular Motor Dismentioning
confidence: 99%
“…30,32 Similar to NP-C, patterns of abnormal saccades can be used to monitor progression of disease. 9,33 Gaucher's disease type 1 is the chronic nonneurological form; however, subtle slowness of saccades has been reported in some patients. 22,[34][35][36] Enzyme replacement therapy and substrate reduction therapy are available.…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%